Assessment of bone mineral density by fractal dimension in OI patients treated with bisphosphonates - Laura Burgueño-Torres; Lara García-Boedo; Manuel Joaquín de Nova-García (BMC Oral Health)
Abstract Background The efficacy of radiographs in studying bone mineral density (BMD) through fractal dimension (FD) analysis represents a conservative method compared to other traditional examinations. Periapical and panoramic radiographs are routine imaging tests in the radiographic evaluation of pediatric patients with Osteogenesis Imperfecta (OI). Anti-resorptive therapies with bisphosphonates constitute the gold standard in the treatment of these patients, and assessing their effectiveness on bone mineral density is essential to determine the necessity of administering any of these drugs or their combinations. Therefore, this study aims to analyze the differences in fractal dimension measured on orthopantomographs of a sample of patients with OI compared to a matched control group. Methods   Panoramic radiographs from 66 patients with OI were analyzed, identifying six regions of interest (ROIs), in mandibular cortical and trabecular bone, using the ImageJ software (version 1.54d). Differences related to the impact of Osteogenesis Imperfecta and the administered anti-resorptive treatment were examined. Statistical analysis of the data was performed with SPSS Statistics 25.0 for Windows. Results The values obtained for ROI 3 showed statistically significant differences between the groups (p 0.002), while ROI 5 yielded values close to statistical significance (p 0.090). When analyzing the influence of antiresorptive therapy in these patients, a strong indication of a relationship was found between the values obtained for ROI 1 and 4 and the administration of zoledronic acid. Conclusions The studied OI patients showed lower bone mineral density compared to healthy controls. The type of OI influenced the fractal dimension values obtained, with those suffering from severe OI being more affected. Although no statistically significant differences were found, the statistical effect size related to zoledronic acid administration suggested a possible direct relationship with the bone mineral density of these patients.